VALUASI EKONOMI LAHAN USAHATANI DI KAWASAN PERI URBAN YOGYAKARTA - Sapto Husodo (Agro Ekonomi, 2004)
Even though under emulation situation of land uses in urban and peri urban area, farm sector in peri urban area still plays important role in giving various benefit such as social, enviromental and economic benefits to the society. this research aims to conduct economic valuation for farmland in peri urband area, analyze farmer readiness to leave the farm activity, analyze the attraction of non farm sector to the farmer that can influence farmer to leave or maintain their activity in farm sector in Yogyakarta peri urban area.The basic method used in this research was CVM method (Contingent Valuation Method). the research located in peri urban are of Yogyakarta and in Yogyakarta municipality region.The existence of total use value of farmland in peri urban area makes the farmers in Yogyakarta oer iurban area and Yogyakarta municipality resident are ready to pay for WTP. The WTP of farmers was related to the locatipn of the farmland.the improved situaation of farm activity will increase the amouunt of farmers who want to remain in farm activity or even they wnat to leave the farm activity under certain condition, which shows that farm activity still being attractive to the farmer. but under this hypothetical situation of improved condition, the tendency of the farmer to leave farm activity under certain condition will go up in lin ewith the increasing of land price and the experience length of the farmer in farm activity. therefore the land price and experience duration in farm activity are the important factor in determining farmer readiness to leave farm activity.whether in existing and improved situation most farmer wish to gain non farm earning as much more than 5 times as earnings of existing farm activity so that they were ready to leave farm activity. this amtter depicts that although there will be improved action in order to repair farm trouble-shooting faced by farmer, the farmer's interest to the non-farm activity did not change.